Question

Find the general solution of the differential equation:

y''' - 3y'' + 3y' - y = e^x - x + 16

y' being the first derivative of y(x), y'' being the second
derivative, etc.

Answer #1

Find the general solution of the following differential
equation:
y^4 - 3y''' + 3y'' - 3y' + 2y = 0

Find the general solution to the non-homogeneous differential
equation.
y'' + 4y' + 3y = 2x2
y(x) =

Find the general solution of the differential equation
y′′−3y′−40y=84e^(2t).

Find the general solution of the differential equation
y′′ − 2y′ − 3y = ae3t, where a is a constant

Find a general solution to the following differential
equation:
4x2y''-3y=0

Find the general solution to the differential equation: y’’ – 6
y’ + 13y = 0
Find the general solution to the differential equation: y’’ +
5y’ + 4y = x + cos(x)

Find the general solution of the x ^ 3y '''- 8x ^ y''+ 28xy'-40y = -9 / x Cauchy-Euler differential equation.

Find the general solution of the equation.
y''-3y'+2y=e^3t

Find the general solution of the following differential
equation. Primes denote derivatives with respect to x.
(x+3y)y'=8x-y

Use an integrating factor to reduce the equation to an exact
differential equation, then find general solution.
(x^2y)dx + y(x^3+e^-3y siny)dy = 0

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 56 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago